The Impact of Education on Personality - Evidence from a German High School Reform - Silke Anger; Sarah Dahmann (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2015)
Western labor markets face major challenges caused by demographic changes. They increasingly experience a shortage of skilled workers and face the problem of an increasing disparity between a reduced group of active workers contributing to the pension scheme and a rising share of an older population receiving pension benefits. Starting in 2001, Germany therefore introduced an educational reform enabling high school graduates earlier labor market entry. By shortening the length of upper secondary school leaving the overall curriculum unchanged, the reform did not only make German graduates more competitive on the international labor market and reduce costs in the German education system, but also increased the labor force by one birth cohort, relieving the shortage of skilled workers and disburdening the pension scheme. However, the reform may have led to unintended consequences on individuals' human capital. This paper investigates this reform's short-term effects on students' personality exploiting the variation in high school duration over time and across states as a quasi-natural experiment. Using rich data from the German Socio-Economic Panel (SOEP) study on adolescents' Big Five personality traits and on their locus of control, our estimates show that shortening high school caused students on average to be less emotionally stable. Moreover, the personality of male students and students from disrupted families changed more strongly following the reform: they became more agreeable and more extroverted, respectively. We conclude that the educational system plays a role in shaping adolescents' personality, which in turn impacts labor market success and further later life outcomes.
Keywords: I21; I28; J24; 330